Soft Scaffolding Strategy: An Adaptive Post-Pandemic Learning to Facilitate Prospective Physics Teacher’s PCK - Nurulsari, Novinta; Abdurrahman, Abdurrahman; Suyanto, Eko; Distrik, I Wayan; Ertikanto, Chandra (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
Teacher professional development programs extensively focus on enhancing teachers’ pedagogical content knowledge (PCK). Given the ongoing programs targeting the improvement of existing teachers’ PCK, there's an evident need for strategies that prepare future educators more effectively. While soft scaffolding has significantly contributed to fostering 21st-century skills among students, its potential in bolstering the PCK of prospective Physics teachers remains under-explored. This study addresses this gap by formulating a soft scaffolding strategy, tailored for post-pandemic learning scenarios, aimed at enriching the PCK of future physics educators. Employing a research and development approach, the ADDIE development design model was utilized. This strategy, termed EPiSODe, integrates key components: Encouraging students, Picking the learning concept, Simulating the learning process, Offering further consultation, and Demonstrating the learning process. Piloted with 52 prospective teachers in Lampung in their third year of Physics Courses, the strategy showcased effectiveness in augmenting their PCK.The results of the data analysis show that the soft scaffolding strategy was effective in increasing the PCK of prospective Physics teachers. The implications of this research include that soft scaffolding learning strategies can be implemented and adapted to the difficulties of candidates in developing PCK competencies. Therefore, to improve the quality of learning for prospective physics teachers and minimize misconceptions or low PCK, this strategy can continue to be developed in case-based learning activities or team-based projects at the higher education level.